Sistem Pakar Diagnosis Adhd (Attention Deficit Hyperactivity Disorder) Pada Anak - Anak Menggunakan Metode Naïve Bayes Berbasis Website - Novan Heru Heryansyah; Angga Suryadi (Journal of Research and Publication Innovation, 2023)
This study aims to develop a website-based expert system that can diagnose ADHD (Attention Deficit Hyperactivity Disorder) in children early based on the symptoms that appear. ADHD is a neurodevelopmental disorder that often appears in children and can have an impact on their growth and development if not properly identified and addressed. Early diagnosis of ADHD symptoms still does not get adequate attention, especially from teachers and parents. This is because many of them do not recognize the symptoms that may appear, and some of these symptoms are often considered normal in the child's growing years. The study used data from a survey conducted at Efata School, which involved a class of 29 children. The data used in the study involved 5 samples from 29 children, including symptoms that appeared in children. The method used in this study was the Naïve Bayes method, which was used to predict whether students at Efata School had symptoms of ADHD. The results of this study showed that one of the students from Efata School suffered from one of the subtypes of ADHD, namely Hyperactivity. It is based on the largest v value found, where the Hyperactivity classification has a value of v = 0.0000028082145115306584428249088, while the v value for the impulsivity classification is 0.0000020302564481111760333385728, and the v value for the inattention classification is 0.0000016957720279202595122184192.